KARAKTERISASI MORFOLOGI VARIETAS JAGUNG KETAN DI KECAMATAN AMPANA KOTA KABUPATEN TOJO UNA-UNA - Yusran Yusran; Maemunah Maemunah (Agroland: Jurnal Ilmu-ilmu Pertanian, 2011)
The  research  aimed  at  inventing  glutinous  corn  cultivar  through  collecting,  characterizing  and identifying  various  characters  of  clustering  glutinous  corn  cultivars  found  in  the  villages  of Tombuo, Padang, Sansarino  and Uentanaga, Ampana Kota  sub district of Tojo Una-Una district. The  research  was  conducted  between  January  and March  2010.  The  research  applied  a  Survey Method and Observations in which the research site was decided based on the information gathered from Department of Agriculture, Plantation, Animal Husbandry and Animal Health of Tojo Una-Una district. Plant, cob and seed morphological characters were observed in order to determine the morphological  diversity  among  the  cultivars  tested.    Dendogram  analysis  was  applied  for identifying the similarities among the tested corn cultivars.  The research findings showed that there are  three  different  cultivar  groups  of  glutinous  corns  with  regard  to  their  morphological characteristics in Kecamatan Ampana Kota. Key Words: Cluster, cultivar, dendrogram, glutinous Corn, morphology.